Xylem K+ loading modulates K+ and Cs+ absorption and distribution in Arabidopsis under K+-limited conditions - Kanno, Satomi; Martin, Ludovic; Vallier, Natacha; Chiarenza, Serge; Nobori, Tatsuya; Furukawa, Jun; Nussaume, Laurent; Vavasseur, Alain; Leonhardt, Nathalie (Frontiers in Plant Science, 2023)
Potassium (K+) is an essential macronutrient for plant growth. The transcriptional regulation of K+ transporter genes is one of the key mechanisms by which plants respond to K+ deficiency. Among the HAK/KUP/KT transporter family, HAK5, a high-affinity K+ transporter, is essential for root K+ uptake under low external K+ conditions. HAK5 expression in the root is highly induced by low external K+ concentration. While the molecular mechanisms of HAK5 regulation have been extensively studied, it remains unclear how plants sense and coordinate K+ uptake and translocation in response to changing environmental conditions. Using skor mutants, which have a defect in root-to-shoot K+ translocation, we have been able to determine how the internal K+ status affects the expression of HAK5. In skor mutant roots, under K+ deficiency, HAK5 expression was lower than in wild-type, although the K+ concentration in roots was not significantly different. These results reveal that HAK5 is not only regulated by external K+ conditions, but it is also regulated by internal K+ levels, in agreement with recent findings. Additionally, HAK5 plays a major role in the uptake of Cs+ in roots. Therefore, studying Cs+ in roots and more detailed information about its uptake and translocation in the plant would be valuable. Radioactive tracing experiments revealed a reduction in the uptake of 137Cs+ and 42K+ in skor mutants compared to wild-type, but also a different distribution of 137Cs+ and 42K+ in tissues. In order to gain insight into the translocation, accumulation, and repartitioning of both K+ and Cs+ in plants, long-term treatment and split root experiments were conducted with the stable isotopes 133Cs+ and 85Rb+. Finally, our findings show that the K+ distribution in plant tissues regulates root uptake of K+ and Cs+ similarly, depending on HAK5, however, the translocation and accumulation of the two elements are different.